2015
DOI: 10.1016/j.phpro.2015.08.263
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Cataract Classification based on Ultrasound Technique Using Machine Learning: A comparative Study

Abstract: This paper addresses the use of computer-aided diagnosis (CAD) system for the cataract classification based on ultrasound technique. Ultrasound A-scan signals were acquired in 220 porcine lenses. B-mode and Nakagami images were constructed. Ninety-seven parameters were extracted from acoustical, spectral and image textural analyses and were subjected to feature selection by Principal Component Analysis (PCA). Bayes, K Nearest-Neighbors (KNN), Fisher Linear Discriminant (FLD) and Support Vector Machine (SVM) cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Dengan 9-fold cross-validation, tingkat klasifikasi tertinggi 91,5% dan 90% dicapai menggunakan model CNN. Caxinha, et al, [5] klasifikasi katarak berdasarkan teknik ultrasound menggunakan klasifikasi Bayes, K-Nearest Neighbours (KNN), Fishes Linear Discriminant (FLD), dan Support Vector Machine (SVM) dengan hasil SVM menunjukkan kinerja tertinggi 90.62%.…”
Section: Pendahuluanunclassified
“…Dengan 9-fold cross-validation, tingkat klasifikasi tertinggi 91,5% dan 90% dicapai menggunakan model CNN. Caxinha, et al, [5] klasifikasi katarak berdasarkan teknik ultrasound menggunakan klasifikasi Bayes, K-Nearest Neighbours (KNN), Fishes Linear Discriminant (FLD), dan Support Vector Machine (SVM) dengan hasil SVM menunjukkan kinerja tertinggi 90.62%.…”
Section: Pendahuluanunclassified
“…Fuadah et al [33] used the KNN to detect cataract on digital camera images and achieved 97.2% accuracy. Literature [12] also uses KNN for cataract classification on Ultrasonic images, which collected from the animal model.…”
Section: Classificationandgradingmentioning
confidence: 99%
“…They found that the computation cost decreased a lot on the basis of new features obtained after PCA transformation with the original result. M. Caixinha et al [13] developed a method which compared four classification techniques. They presented a method based on ultrasound technique using machine learning algorithm for Automatic Cataract Classification.…”
Section: Related Workmentioning
confidence: 99%